INNOVATION, ENTREPRENEURSHIP, AND COMPETITIVE ADVANTAGE IN LOMBOK’S KETAK CRAFT MSMEs - Niazi, Hakam Ali (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
MSMEs in Lombok, especially those in handicrafts rooted in local wisdom, have significant potential for regional economic growth. One key product from Lombok is ketak craft, made from the natural fibers of the ketak fern, which is found abundantly in West Nusa Tenggara. However, only about 25% of MSMEs have managed to survive and remain competitive over the past five years. A survey revealed that 60% of MSMEs in the ketak craft sector faced stagnation due to limited capital, lack of innovation, and restricted access to global markets. This study aims to analyze the factors that influence competitive advantage and SME performance, namely Innovation Capability and Entrepreneur Orientation. The population of this study was all ketak craft SMEs located in the craftsman centers of West Lombok, Central Lombok and East Lombok. Because the number of ketak craft SMEs is quite large, the Cochrane formula was used to calculate the number of samples for an unknown population of 96 respondents. The data analysis technique used Structural Equation Modeling (SEM). The results of the study showed that innovation capability, entrepreneur orientation had a significant influence on competitive advantage and competitive advantage was able to influence SME performance.